Influence of coronary artery disease and percutaneous coronary intervention on mid‐term outcomes in patients with aortic valve stenosis treated with transcatheter aortic valve implantation. Issue 8 (25th May 2021) - Kaihara, Toshiki; Higuma, Takumi; Izumo, Masaki; Kotoku, Nozomi; Suzuki, Tomomi; Kameshima, Haruka; Sato, Yukio; Kuwata, Shingo; Koga, Masashi; Mitarai, Takanobu; Watanabe, Mika; Okuyama, Kazuaki; et al.
Abstract: Background: A high frequency of coronary artery disease (CAD) is reported in patients with severe aortic valve stenosis (AS) who undergo transcatheter aortic valve implantation (TAVI). However, the optimal management of CAD in these patients remains unknown. Hypothesis: We hypothesis that AS patients with TAVI complicated by CAD have poor prognosis. His study evaluates the prognoses of patients with CAD and severe AS after TAVI. Methods: We divided 186 patients with severe AS undergoing TAVI into three groups: those with CAD involving the left main coronary (LM) or proximal left anterior descending artery (LAD) lesion (the CAD[LADp] group), those with CAD not involving the LM or a LAD proximal lesion (the CAD[non‐LADp] group), and those without CAD (Non‐CAD group). Clinical outcomes were compared among the three groups. Results: The CAD[LADp] group showed a higher incidence of major adverse cardiovascular and cerebrovascular events (MACCEs) and all‐cause mortality than the other two groups (log‐rank p = .001 and p = .008, respectively). Even after adjustment for STS score and percutaneous coronary intervention (PCI) before TAVI, CAD[LADp] remained associated with MACCE and all‐cause mortality. However, PCI for an LM or LAD proximal lesion pre‐TAVI did not reduce the risk of these outcomes. Conclusions: CAD with an LM or LAD proximal lesion is a strong independent predictor of mid‐term MACCEs and all‐cause mortality in patients with severe AS treated with TAVI. PCI before TAVI did not influence the outcomes.